A Benders decomposition algorithm for the order fulfilment problem of an e-tailer with a self-owned logistics system. (February 2019) - Li, Shuqin; Jia, Shuai
Highlights: A new e-tail order fulfilment problem is studied. A MIP formulation is developed and its computational complexity is analyzed. A Benders decomposition algorithm is proposed for solving the problem. Test instances are generated from the logistic network of JD.com. Abstract: This paper studies an order fulfilment problem in an e-tailing environment, where the e-tailer fulfills orders by assigning orders to its fulfilment centers and routing the shipments from the fulfilment centers to its delivery stations. We develop a mixed integer program for the problem, analyze its computational complexity, and propose a Benders decomposition algorithm for solving the problem. Computational performance of the proposed algorithm is evaluated on problem instances generated based on the logistics network of JD.com in Shanghai. Computational results show that the Benders decomposition algorithm is able to achieve satisfactory performance within reasonable computation time.